Bio-mineralisation, characterization, and stability of calcium carbonate containing organic matter. Issue 24 (19th April 2021) - Liu, Renlu; Huang, Shanshan; Zhang, Xiaowen; Song, Yongsheng; He, Genhe; Wang, Zaifeng; Lian, Bin
Abstract : The amorphous calcium carbonate (ACC) or polycrystalline vaterite, which has long-term water stability and thermal stability, can be induced by bacteria. These biogenic CaCO3 are organo-mineral complexes. Abstract : The composition of organic matter in biogenic calcium carbonate has long been a mystery, and its role has not received sufficient attention. This study is aimed at elucidating the bio-mineralisation and stability of amorphous calcium carbonate (ACC) and vaterite containing organic matter, as induced by Bacillus subtilis . The results showed that the bacteria could induce various structural forms of CaCO3, such as biogenic ACC (BACC) or biogenic vaterite (BV), using the bacterial cells as their template, and the carbonic anhydrase secreted by the bacteria plays an important role in the mineralisation of CaCO3 . The effects of Ca 2+ concentration on the crystal structure of CaCO3 were ascertained; when the amount of CaCl2 increased from 0.1% (m/v) to 0.8% (m/v), the ACC was transformed to polycrystalline vaterite. The XRD results demonstrated that the ACC and vaterite have good stability in air or deionised water for one year, or even when heated to 200 °C or 300 °C for 2 h. Moreover, the FTIR results indicated that the BACC or BV is rich in organic matter, and the contents of organic matter in biogenic ACC and vaterite are 39.67 wt% and 28.47 wt%, respectively. The results of bio-mimetic mineralisation experiments suggest that the protein secreted by bacterial metabolism may be inclined to inhibit the formation of calcite, while polysaccharide may be inclined to promote the formation of vaterite. Our findings advance our knowledge of the CaCO3 family and are valuable for future research into organic-CaCO3 complexes.